1993
DOI: 10.1152/ajpheart.1993.265.4.h1209
|View full text |Cite
|
Sign up to set email alerts
|

Kallikrein release by vascular tissue

Abstract: Vascular tissue contains kallikrein and kallikrein mRNA, suggesting a vascular kallikrein-kinin system. We questioned whether 1) kallikrein concentration varies among large and small vessels; 2) kallikrein is released by vascular tissue; and 3) blocking protein synthesis inhibits release, suggesting de novo synthesis. Using rat vascular rings and isolated-perfused hindquarters, we examined kallikrein in the bath and perfusate. Active kallikrein was higher in tail arteries than the aorta (P < 0.001); tail veins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…On the other hand, we and others have shown that components of the kallikrein-kinin system are found in the heart (11,54,55), while kinins are found in the effluent of isolated perfused hearts and are increased by ACEi as well as by ischemia (56, 57). Furthermore, ACEi significantly increase kinin concentrations in the heart and vascular tissue (58).…”
Section: Discussionmentioning
confidence: 96%
“…On the other hand, we and others have shown that components of the kallikrein-kinin system are found in the heart (11,54,55), while kinins are found in the effluent of isolated perfused hearts and are increased by ACEi as well as by ischemia (56, 57). Furthermore, ACEi significantly increase kinin concentrations in the heart and vascular tissue (58).…”
Section: Discussionmentioning
confidence: 96%
“…its action as an antioxidant, as a mitogen, or as an antiinflammatory agent (57-60)? Second, do other proteases present in the aortic intima that are capable of cleaving apoA-I, such as plasmin, thrombin, kallikrein, and elastase (42,61,62), also block cholesterol efflux? Interestingly, SDS-PAGE analysis of a major fibril protein purified from amyloid deposits in the aortic intima revealed two broad bands corresponding to ϳ14 and Ͻ10 kDa, which were shown to be NH 2 -terminal fragments of apoA-I (63).…”
Section: Fig 6 Proteolytic Degradation Of Hdlmentioning
confidence: 99%
“…In addition, the expression of a kiningenerating member of mouse glandular kallikrein was detected in mouse kidney (28). We performed our studies in the presence of soybean trypsin inhibitor, which, at a concentration of 2 mg/ml, caused 73.3% of inhibition of the amidase activity of human leukocyte extracts (20) and which did not inhibit glandular (renal) kallikreins (29). Thus, we cannot rule out the possibility that our results could probably represent additive activities of both renal and leukocyte enzymes.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, we cannot rule out the possibility that our results could probably represent additive activities of both renal and leukocyte enzymes. Future studies in the presence of SBTI + EDTA + aprotinin should be performed to evaluate independently renal kallikrein-like amidase activities from leukocyte or other proteases (29).…”
Section: Discussionmentioning
confidence: 99%